Congenital spinal cord haemangioblastoma: another cause of spinal cord section syndrome in the newborn. Issue 8 (August 1988) - Roig, M; Ballesca, M; Navarro, C; Ortega, A; Martorell, R; Fina, A
Abstract : A newborn infant with negative perinatal history and characteristic clinical findings of upper cervical spinal cord section is described. Metrizamide myelography performed on the 7th and 22nd days of life was negative. Peroneal somatosensory evoked responses showed a conduction block at the cervical level. Necropsy revealed a haemangioblastoma extending from levels C1 to C5.